Eco prints: dyeing and printing with plants - Haar, Sherry J. (Kansas State University, 2011)
Sustainable fashion is part of the growing design philosophy of sustainability, with goals to create systems which can be supported indefinitely in terms of environmentalism, economics, and social responsibility. Growing natural dyestuffs is beneficial to the environment, provides an alternative to petro-chemical based dyes, and supports the sustainable tenets of slow design, small scale production, and regional expertise (Fletcher, 2008). Information on dyeing solid colors with flowers is available; however, there is less information regarding multi-colored effects from dyeing with flowers. Therefore, my scholarship focuses on low tech, hand methods of bundling, pressing and hammering to create multi-colored textile surface design from regional flowers using solar and decomposition methods to extract the color. I grow over 30 types of dye plants in my garden, however, many trees and plants in the wild are appropriate for dyeing. In addition, some plants that do not produce good dye bath colors, work well for other color extraction techniques such as hammering. Garment designs are informed by the eco printed fabrics with a consciousness of minimizing waste; therefore, use of the draped square and rectangle are prevalent.
Keywords: Natural dyes; Textiles; Sustainability; Fashion